2008
DOI: 10.4049/jimmunol.180.4.2625
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Is Critically Involved in Infarct Healing by Regulating the Inflammatory and Fibrotic Response

Abstract: Infarct healing is dependent on an inflammatory reaction that results in leukocyte infiltration and clearance of the wound from dead cells and matrix debris. However, optimal infarct healing requires timely activation of “stop signals” that suppress inflammatory mediator synthesis and mediate resolution of the inflammatory infiltrate, promoting formation of a scar. A growing body of evidence suggests that interactions involving the transmembrane receptor CD44 may play an important role in resolution of inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(156 citation statements)
references
References 35 publications
3
151
1
1
Order By: Relevance
“…CD44 also exerts fibrogenic actions mediating fibroblast migration and invasion in the wound provisional matrix [285]. Recent experiments from our laboratory tested the hypothesis that CD44 may play an essential role in infarct healing by regulating the inflammatory and fibrotic response [286]. We found that CD44 null mice exhibit enhanced and prolonged inflammation in the infarcted heart followed by reduced myofibroblast infiltration.…”
Section: Clearance Of Apoptotic Neutrophils and Removal Of Matrix Debrismentioning
confidence: 85%
“…CD44 also exerts fibrogenic actions mediating fibroblast migration and invasion in the wound provisional matrix [285]. Recent experiments from our laboratory tested the hypothesis that CD44 may play an essential role in infarct healing by regulating the inflammatory and fibrotic response [286]. We found that CD44 null mice exhibit enhanced and prolonged inflammation in the infarcted heart followed by reduced myofibroblast infiltration.…”
Section: Clearance Of Apoptotic Neutrophils and Removal Of Matrix Debrismentioning
confidence: 85%
“…This would occur if such cells were dependent on CD44-mediated "homing" to the site, as has been reported for inflammatory cells and fibroblast progenitors (45,46). Such a deficiency of progenitors in the absence of CD44 would also reduce the total number of cells capable of responding to TGF␤1 to restore the dermal collagen matrix.…”
Section: Discussionmentioning
confidence: 96%
“…In experimental models, release of type I collagen fragments in the serum has been documented within 30 minutes after coronary occlusion (37). Fragmentation of components of the basement membrane, such as collagen IV, and of noncollagenous matrix constituents has also been demonstrated in the infarcted myocardium (38)(39)(40)(41). Low-molecular weight hyaluronan fragments exert potent proinflammatory actions in the infarcted region; impaired clearance of these fragments has been shown to prolong and accentuate proinflammatory signaling in leukocytes and vascular cells (42,43).…”
Section: Ecm During the Proliferative Phase Of Infarct Healingmentioning
confidence: 99%
“…In vitro, pericellular hyaluronan was required to maintain a myofibroblast phenotype in TGF-β-stimulated cells (67). In vivo, loss of CD44, the main receptor for haluronan, impaired collagen synthesis in infarct fibroblasts (40). Versican loss in dermal fibroblasts attenuated myofibroblast conversion (68).…”
Section: Ecm During the Proliferative Phase Of Infarct Healingmentioning
confidence: 99%